HUBUNGAN PENGETAHUAN PERAWAT TENTANG UNIVERSAL PRECAUTION TERHADAP KEPATUHAN PRINSIP-PRINSIP PENCEGAHAN INFEKSI - Kosasih, M Ikhwan; Anjarsari, Ika Dewi (Jurnal AKP, 2012)
Health worker have a role in infection control that is to keep the health and safety of themselves and others consequently need a behavior to prevent infection by a principle of obedience to minimize infection. The purpose of this research is to know the relation of nurseâs knowledge about Universal Precaution toward obedience principles of infection prevention.The Research design was cross sectional analytic that emphasizes the time of measurement and observation only once in a while. The population in this research were all the nurses in Seruni and Cempaka RSUD Pare in 2010 amount to 34 respondents. Sampling method used total sampling. data analysis used Spearman correlation.Results of research about the knowledge of Universal Precaution showed 73.5% had adequate knowledge about Universal Precaution, 14.7% have less knowledge, and 11.8% had good knowledge, while the results of research for compliance toward the principles of infection prevention that is 2.4 % moderate and 17.6% obedience to apply the principles of infection prevention. From the results of research and analysis, there is a very strong relation between knowledge of the Universal Precaution toward obedience principles of infection prevention.The above matter is possible because of the lack of information for nurses so that nurses should strive to improve obedience in carrying out the principles of infection prevention and trying to find information about universal precaution.several factors, including the factors of culture, beliefs and also the resources (facilities, money, time, and energy)